Implementation of make a match model to improve thematic learning outcomes - Susanti, Heni; Radia, Elvira Hosein (Universitas Pendidikan Ganesha, 2019)
Curriculum 2013 focuses on the implementation of thematic learning; thus requires a suitable model of approach to improve student learning outcomes. The purpose of this study was to apply make a match learning model to Curriculum 2013 Theme 7 and analyze its influence to improve learning outcomes in primary school students. This classroom action research was conducted in 2 cycles at SDN Kutowinangun 10 Salatiga with a study sample of 16 students in class IV. Each cycle had 4 stages, i.e. planning, action, observation, and reflection. Data collection techniques used were tests and observations. Result shows an increase in students' learning outcomes indicated by an increase in the number of students who passed the Minimum Completion Criteria, i.e. from 37.5% in cycle 1 to 81.25% at the end of cycle 2. Therefore, make a match cooperative model could be implemented by teachers to improve the quality of learning in the classroom.